Analysis characteristic and performance of passive Radio Frequency Identification (RFID) for 13.56MHz system / Mohd Faizul Azmy Amat - Amat, Mohd Faizul Azmy (2007)
Now a day world technology of RFID will used in a global security of identifications. This technical paper is consist the analysis of development of RFID for low range frequency coverage for passive RFID 13.56MHz. Scope of work include the algorithm for RFID flow in which frequency band will be continually implemented considering pre-determined constraints. Hence optimization technique will also be incorporated in this work analysis.